A mouse model of chronic idiopathic pulmonary fibrosis. Issue 2 (25th February 2014) - Limjunyawong, Nathachit; Mitzner, Wayne; Horton, Maureen R.
Abstract Chronic idiopathic pulmonary fibrosis (IPF) is a progressive, fatal, and untreatable disease with unclear etiology. There are few models of this chronic pathology, and although delivery of bleomycin to induce acute lung injury is the most common animal model of pulmonary fibrosis, there is considerable uncertainty about whether this acute injury resolves in those animals that survive. In this report, we have systematically followed groups of mice for up to 6 months following a single insult of bleomycin. We assessed changes in lung function and pathology over this time course, with measurements of the diffusion capacity for carbon monoxide, lung mechanics, quantitative stereology, and collagen. Our results show that, while there is some repair over this extended time course, the injury in the lung never fully resolves. This persistent degree of fibrosis may have similarities to many features of human IPF. Thus, these chronic fibrotic changes in mouse lungs could be a useful model to evaluate potential therapeutic interventions to accelerate repair and possible treat this debilitating disease.